2023
DOI: 10.3389/fimmu.2023.1217366
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin1: insight into inflammatory conditions and its potential involvement in multiple organ dysfunction syndrome

Xiangyu Chen,
Siyi Yuan,
Liangyu Mi
et al.

Abstract: Sepsis represents a global health concern, and patients with severe sepsis are at risk of experiencing MODS (multiple organ dysfunction syndrome), which is associated with elevated mortality rates and a poorer prognosis. The development of sepsis involves hyperactive inflammation, immune disorder, and disrupted microcirculation. It is crucial to identify targets within these processes to develop therapeutic interventions. One such potential target is Panx1 (pannexin-1), a widely expressed transmembrane protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“… 178 In addition, there are many reagents that inhibit the channels formed by Panxs and Cxs, but more inhibitory mechanisms have yet to be explored. 179 , 180 …”
Section: Perspective Of Panxs In Musculoskeletal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“… 178 In addition, there are many reagents that inhibit the channels formed by Panxs and Cxs, but more inhibitory mechanisms have yet to be explored. 179 , 180 …”
Section: Perspective Of Panxs In Musculoskeletal Systemmentioning
confidence: 99%
“…178 In addition, there are many reagents that inhibit the channels formed by Panxs and Cxs, but more inhibitory mechanisms have yet to be explored. 179,180 In various diseases, targeting Cxs has proven to be an effective therapeutic approach by either permanently or temporarily closing the channels. This strategy holds great potential for systematic research and targeted therapy of Panxs in the future.…”
Section: Perspective Of Panxs In Musculoskeletal Systemmentioning
confidence: 99%
“…The release of MMPs by transformed VSMCs in AAA leads to the accelerated breakdown of the extracellular matrix ( 109 ), and similar mechanisms are observed in AD where altered VSMC phenotype contributes to the progression of the dissection ( 106 ). Additionally, the involvement of specific pathways like the pannexin-1 (Panx-1)/P2Y2 receptor pathway in VSMC activation indicates shared molecular targets that could be explored for therapeutic interventions in both conditions ( 110 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xing et al [ 3 ] provide promising insights into how Panx1 facilitates inflammatory pain through experiments on pain sensitivity and neuronal excitability. Few studies have demonstrated the translational progress of Panx1 as the target for inflammation and disease control [ 11 13 ], so further research characterizing the interactions of pharmacological treatments on Panx1, the Wnt/β-catenin signaling pathway, and DRG may elucidate promising avenues for the treatment of chronic pain in the military population.…”
mentioning
confidence: 99%